Perancangan Usaha Pembukaan Cabang Baru pada Rumah Makan - Syifa Salsabila; Endang Chumaidiyah; Yudha Prambudia (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine the estimated market demand at branch locations by calculating using forecasting methods. This calculation is estimated for the next five years. On the technical and operational aspects, the calculation of operational costs and investment costs is carried out as well as determining the location for the opening of the Sop Buntut Cut Meutia business branch. On the financial aspect, the investment is calculated whether it is feasible or not. The determinant of a business is said to be feasible if it has an NPV value > 0, IRR > MARR. The results showed that the results of the design of the oxtail soup branch opening business obtained an NPV value of IDR 252,216,017 with an IRR value of 29.64% and a MARR value of 8.25%. In conclusion, the business plan to open a new branch in the cut meutia oxtail soup business is considered feasible. Keywords: IRR, NPV, PBP, Business Design, Business Feasibility Study